EVALUATION OF ENDODONTIC IRRIGANTS EFFECTS ON THE ROOT CANAL DENTIN WALL - Corina Alexandra (Concită); Mihaela Sălceanu; Anca Melian; Raluca Dragomir; Elena Gabriela Hitruc; I. Taraboanta; C. L. Giuroiu; S. Andrian (Romanian Society of Oral Rehabilitation, 2024)
The associations of ethylenediaminetetraacetic acid (EDTA) and citric acid (AC) with sodium hypochlorite (NaOCl) are combinations used for cleaning and disinfecting of the root canals. The aim of this in vitro study was to evaluate by AFM the effect of 20% EDTA and 40% AC associated with 5,25% NaOCl in root canal SL removal and on root dentine surface rough-ness. Fifteen extracted single-root teeth were randomly divided into 3 groups according to the irrigation method: in Group 1, samples were irrigated with 5 mL of 5.25% NaOCl followed by 5 mL of 20% EDTA solution for 1min; in Group 2, samples were irrigated with 5 mL of 5.25% NaOCl solution followed by 5 mL of 40% AC solution for 1min; in Group 3 samples were irri-gated with 5 mL of 0.9% physiological serum. AFM was used to obtain 2D and 3D images and roughness parameters (Sa, Sq). The data was statistically analyzed using significance F-test, ANOVA and post-hoc Bonferroni test. The images obtained by AFM highlighted free dentinal tubules in the coronal and middle third of the root canal in Group 1, partially free dentinal tu-bules in the coronal and middle third in Group 2, while in Group 3 opening of the dentinal tu-bules were not observed. The lowest mean Sa values were recorded by Group 3. Group 1 and 2 presented significantly higher mean values of Sa, Sq, in comparison with the Group 3 in all areas of the root canal (p<0,05). Also, in the Group 1 the mean values of Sa, Sq, were higher than Group 2, especially in the coronal and apical third where the differences being statistically significant (p<0,05). The association of 20% EDTA with 5.25% NaOCl solutions in the irrigation of the en-dodontic system is more efficient in removing SL in the coronal and middle thirds of the root canal and increases the root dentin surface roughness in all areas in comparison with 0,9% phys-iological serum and in the coronal and apical third in comparison with 40% AC with 5,25% NaOCl.